News Paper Photographs and Election Coverage at Geographical levels: A study of Telugu newspapers - Anita, Dr. G.; Babu, T. Yogesh (The journal of contemporary issues in business and government, 2021)
Due to the ever growing competition from television and internet the newspapers have been opting for in-depth analysis, background information, unique coverage, richness of narrative and better visuals which was visible in the pages. According to Sliwinski (2011) images play an important role in promoting the development of civil privileges due to wide circulation, especially during disasters and conflicts. It helps to create a global audience and to enhance better understanding of a common civilization. Many studies explored the issues of proximity and location between the scene and it was felt, spatially and temporally, by focusing on the relationship between mass-produced images of disasters, wars, conflicts, and public reactions to the photos taken as they pay more attention and notice the emergence of a global community of viewers. The researchers tried to find out how the top newspapers presented the photographs in the coverage of politics and election process along with the news, stories and others during the elections held in 2019 in the state of Andhra Pradesh. The study attempted to analyze the focus of news photographs on regional and national issues published by newspapers. Four newspapers were selected and all the photographs published in a total of three months study period were considered as the sample. The results show that at Geographical level more coverage was given to the state as well as the national level issues compared to the local issues. Though the newspapers belong to the local vernacular languages the agenda has been mostly on the national issues and politics.